Pegilated interferon alpha 2b «Pegaltevir» chronic hepatitis C treatment (randomized clinical trial) - Marina V. Mayevskaya; Ye. N. Bessonova; P. O. Bogomolov; N. I. Geyvandova; K. V. Zhdanov; V. G. Morozov; V. D. Pasechnikov; I. Yu. Khomenko; A. V. Yagoda; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Nowadays the question, whether pegylated interferon should be completely abandoned in the treatment of chronic hepatitis C (CHC) is still open. Beneficial interferon properties include: absence of mutagenic capacity for hepatitis C virus and drug interaction, stimulation of host immune response. These qualities formed the basis for development of the Russian pegilated interferon-alpha 2b (Pegaltevir®, LLC «FARMAPARK», Russia) and carrying out doublestaged randomized open clinical trial: study of safety, tolerability and pharmacokinetics of Pegaltevir® at single injection of increasing doses in various groups of healthy volunteers - the I stage; studying of efficacy and safety of Pegaltevir® in comparison to PegIntron® (Schering-Plough, USA) at CHC as a part of double antiviral therapy with ribavirin (Rebetol®, Schering-Plough, USA) - the II stage. This article presents results of the II phase of investigation. Material and methods. Original study included 140 adult antiviral treatment-naive patients with CHC and compensated liver function. Patients (aged 18 to 70 years) were distributed into four groups. Group 1 (main group, Pegaltevir®/Rebetol® treatment) - 55 patients, HCV genotype 1; group 2 (comparison group, PegIntron®/Rebetol® treatment) - 20 patients, HCV genotype 1; group 3 (main group, Pegaltevir®/Rebetol® treatment) - 47 patients, non-genotype 1 (2 and 3); group 4 (comparison group, PegIntron®/ Rebetol ® treatment) with non-genotype 1 (2 and 3). Assessment of Pegaltevir® efficacy was carried out in 4 weeks (rapid virologic response, RVR) and 12 weeks of treatment (early virologic response, EVR) in groups 1 and 3 in comparison to corresponding scores in groups 2 and 4 (primary criteria of efficacy were estimated in all 140 patients enrolled in original study. The response rate at the moment of secession of antiviral therapy, the sustained virologic response (SVR), histologic response (comparison of paired liver biopsies) served as secondary efficacy criteria and were estimated in 129 patients who completed treatment. The safety analysis was carried out for each patients included in the protocol who received at least one Pegaltevir® dose in comparison to patients who received at least one dose of PegIntron®, - respectively 102 and 38 patients. Results. RVR was comparable in the Pegaltevir® and PegIntron® groups: 65,6 and 82,4% respectively (p>0,05). RVR frequency genotype one patients was 45,3% in Pegaltevir® treatment group and 66,7% in PegIntron® treatment group (p>0,1). At patients with non-genotype 1 (2 and 3): 92,5 and 100% respectively (p>0,05). RVO did not significantly differ in the studied groups: 91,6 and 97,1% for all genotypes respectively (р>0,1). RVO rate for genotype 1 patients in Pegaltevir® group was 86,8%, in PegIntron® treatment group - 94,4% (р>0,1), in non-genotype 1 patients (2 and 3) it reached 97,6 and 100% in the specified patient groups (р>0,1). Response rate at the moment of treatment secession for Pegaltevir® and PegIntron® was 87,4 and 97,1% respectively for all genotypes (р>0,05). In patients with HCV genotype 1 this score Pegaltevir® treatment group reached 79,3%, in PegIntron® group - 94,4% (р> 0,05), in non-genotype 1 patients (2 and 3) - 97,6 and 100% respectively (р>0,1). SVR rate at Pegaltevir® treatment was 82,1% (for all genotypes), PegIntron® - 82,4% (for all genotypes, p>0,1). In HCV genotype 1 patients in Pegaltevir® treatment group SVR made 73,6%, in PegIntron® treatment group - 83,3%, p>0,1, for non-genotype 1 (2 and 3) - 92,9 and 81,3%, p>0,1. No significant differences between basic and control groups at analysis of paired liver biopsies for fibrosis stage reduction rate, absence of negative changes for fibrosis severity and proportion of patients with fibrosis progression were found. Pegaltevir® and PegIntron® treatment groups were comparable safety profile, adverse events were expected, mainly of mild and moderate severity. Conclusion. The hypothesis of identical efficacy of the Russian drug Pegaltevir® tested in the protocol in comparison to PegIntron® was correct and proved. Safety of Pegaltevir® was comparable to safety of PegIntron® as well.